PENERAPAN BAGIAN WARISAN ANAK PEREMPUAN DAN CUCU: (Studi kasus KHI pasal 176) - Syuhada Syuhada (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2020)
Abstract: Inheritance is a complex problem that sometimes many people do not know the parts and the amount of distribution in order to divide and distribute inheritance. To complete the distribution of the inheritance, many fuqoha 'practice interpreting the verses of the Koran in order to give laws to parts of the inheritance that are not explicitly stated in the Koran and Hadith, for example in this article are part of the inheritance of the grandchildren. women who are not listed in the text but then the Fuqoha 'equate their share with the inheritance of the daughter.